Urogenital Manifestations in Mpox (Monkeypox) Infection: A Comprehensive Review of Epidemiology, Pathogenesis, and Therapeutic Approaches - He S; Zhao J; Chen J; Liang J; Hu X; Zhang X; Zeng H; Sun G (Infection and Drug Resistance)
Sike He,* Jinge Zhao,* Junru Chen, Jiayu Liang, Xu Hu, Xingming Zhang, Hao Zeng, Guangxi Sun Department of Urology, Institute of Urology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Guangxi Sun; Hao Zeng, Department of Urology, Institute of Urology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China, Email sungx077@126.com; kucaizeng@163.comAbstract: Monkeypox (mpox), caused by mpox virus (MPXV) infection, reemerged in 2022 and still raises concerns globally. Abundant clinical data indicate that mpox is a sexually transmitted infection and that the urogenital system is the most frequently involved system in mpox, which deserves more attention. Penile lesions are the most common presentation, followed by urethritis. Acute urine retention and acute kidney injury are relatively rare but also highly crucial. Currently, the majority of the urogenital lesions are considered complications secondary to MPXV infection and the common immunosuppression in mpox patients. However, such viewpoints should be treated carefully due to the lack of understanding of the basic mpox pathology. Here, we briefly and comprehensively review the current evidence concerning urogenital lesions caused by mpox, including epidemiology, clinical features, pathogenesis, and therapeutic approaches to provide a preliminary reference for clinicians in future clinical practice.Keywords: mpox, mpox virus, sexually transmitted infection, urogenital lesion, urologist